Relativistic anisotropic stellar models with Tolman VII spacetime - Bhar, Piyali; Murad, Mohammad Hassan; Pant, Neeraj (© 2015, Springer Science+Business Media Dordrecht, 2016)
This article was published in the Astrophysics and Space Science [© 2015, Springer Science+Business Media Dordrecht] and the definite version is available at : http://dx.doi.org/10.1007/s10509-015-2462-9. The Journal's website is at: http://link.springer.com/article/10.1007%2Fs10509-015-2462-9